Document Support for Modern Management: Competency-based Approach - ANDRUNIK, Andrey P.; DROBYSHEVA-RAZUMOVSKAYA, Lyudmila I.; DUBROVSKY, Alexander V.; TSARIYEV, Evgeniy A.; MURALEV, Andrey A. (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015DO - 10.14505/jarle.v6.1(11).02, 2016)
Numerous studies conducted in different countries have revealed a direct link between the level of personnel competence and innovation performance of the company, which may be expressed in a practical ability to effectively apply knowledge and skills in solving professional problems. However, analysis of the tasks set out in the framework of a new paradigm ‘Management 2.0’ leads to the conclusion that the question of the development of new models of competencies that can bring the modern enterprise management to a new level remains open. The article discusses the relevance of the forming document support competence in future managers and the need to improve vocational training of students in Russian universities. The scientific objective of this study is to justify the process of forming document support competence in vocational training of students in universities on the basis of the developed and tested model of forming document support competence. As a hypothesis, the study examines the assumption that the effective formation of document approach competence of graduates will be achieved through implementation in the learning process of students of a specialized training course in conjunction with a complex of pedagogical conditions of effective formation of document support competence.
Keywords: competence, competency, document, document science, document support, document support competence